USING MIND MAPPING TECHNIQUE TO IMPROVE THE STUDENTS’ READING COMPREHENSION OF RECOUNT TEXT - Niken Athifah Alya Fitri; Chyntia Heru Woro Prastiwi; Oktha Ika Rahmawati (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Reading is a vital skill for junior high school students as it is tested in the national assessment. Unfortunately, they often experience comprehension difficulties such as confusion about the meaning of words or sentences, inability to connect ideas in a passage, omission of or glossing over details, difficulty distinguishing significant information from minor details, and lack of concentration during reading. This classroom action research aims to improve reading comprehension by using mind-mapping techniques on the eighth graders of SMPIT Insan Permata, Bojonegoro. Field notes, observation checklists, interviews, questionnaires, and reading tests were used to collect data. The results of the field note showed that the mind mapping technique was 96.7% employed properly in the classroom based on the teaching plan. Furthermore, the result of the interview demonstrated that the mind mapping technique could solve their reading problems and help them understand a text. The results of the observation checklist also indicated that all students were actively involved and gave positive responses during the implementation of the mind mapping technique. Meanwhile, results from pre-and post-questionnaires revealed that previously uninterested students became more active, enthusiastic, and motivated in comprehending a text. The results from the preliminary test and the tests of cycles 1 and 2 indicated that the students’ average scores kept improving from 53.18, 76.36, and 95.45. In addition, the total number of students passing the minimum score of 75 also kept increasing, subsequently by 2, 7, and 11 students in the preliminary test, test 1, and test 2. In conclusion, the mind mapping technique was successful in improving the students’ reading comprehension of recount text.